Analysis Of The Influence Of Online Consumer Reviews And Influencers On Trust In Reaching Online Cosmetics Purchasing Decisions Among Gen Z - Arridho, Agung; Sinaga , Betrand Orlando; Satrio , Yogi Agung (Journal of Business, Management, and Social Studies, 2023)
Objective – The aim of this research is to analyze the influence of Consumer Online Reviews and Influencers on Trust in achieving Gen Z purchasing decisions. Methodology – The data in the study were analyzed using Smart-PLS software. This study collected 70 Gen Z samples. Evaluation is carried out with the outer model and the inner model to ensure the robustness of the proposed model. Findings – The results obtained show that online consumer and brand trust have a direct and significant influence on online purchase decisions. As already calculated, we also obtained results showing that influencer affect and transaction trust do not have a direct and significant influence on online purchase decisions. Novelty – This research analyzes the combined influence of Consumer Online Reviews (COR) and the influence of influencers on purchasing decisions. The combination of these two variables provides a more comprehensive understanding of the factors that influence Gen Z’s online purchasing decisions.